Introduction to the Special Issue - David C. Thompson; Faith E. Crampton; R. Craig Wood (Educational Considerations, 2012)
This special issue of Educational Considerations presents a selection of papers from the inaugural National Education Finance Conference held in 2011.
Keywords: National Education Finance Conference; Children; United States